PENINGKATKAN KETAHANAN KUALITAS PRODUK MELALUI BANTUAN PENGEMASAN PRODUK DAN PENGENALAN PEMASARAN DIGITAL PADA USAHA MIKRO KECIL OLEH OLEH KHAS TRENGGALEK - Rofiaty; Sumiati; Oktaria Ardika Putri (Universitas Kadiri, 2025)
MSEs from the typical city of Trenggalek are the targeted targets for community service implementation. Through the creation of Instagram content, product content, QRIS, and initiatives to improve the attractiveness of items with good packaging that can last longer, the goal of this activity is to promote product durability and market coverage so that it is more well-known in other areas. In addition to making the product more robust, high-quality, long-lasting, and less prone to damage, the goal is to boost its competitiveness by offering stickers to help with product packaging, which should encourage entrepreneurs and lead to more prosperous enterprises. Since they have typically been entrepreneurs for decades—even in the second generation or more—this practice will help them to become more tough, robust, and unflappable when dealing with the problems of a chaotic and quickly changing world. Since the next generation must remain youthful at heart, they will also be introduced to entrepreneurial traits, such as being loyal to God Almighty, honest, imaginative, and creative, having a strong sense of self-worth, having the guts to take quantifiable business risks, and enjoying change. surroundings.